Crushed conglomerates of Teteriv series in Ukrainian Shield (According whith the data of tectonofacial investigations) - LUKIIENKO, O.; YANCHENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article presents the results of tectonofacial investigations of conglomerate-like rocks of Teteriv series (Paleoproteozoic) in Ukrainian shield. The grounding of these rocks dislocation origin is adduced. Their textural characteristics, physical conditions and formation mechanism are analyzed.